Dark matter EFT, the third: neutrino WIMPs - Bischer, Ingolf; Plehn, Tilman; Rodejohann, Werner (SciPost physics, 2021)
SciPost Journals Publication Detail SciPost Phys. 10, 039 (2021) Dark Matter EFT, the Third -- Neutrino WIMPs
Gesehen am 02.06.2021